Long-chain chlorinated paraffins (LCCPs) exposure induces apoptosis in primary chicken embryo hepatocytes through oxidative stress - Haochu Deng; Yezi Taishi; Guoxia Wang; Yuebing Kong; Ruoting Zhang; Xin Zheng (Ecotoxicology and Environmental Safety)
Long-chain chlorinated paraffins (LCCPs) are industrial raw materials extensively utilized worldwide. Recently, their environmental impact has escalated, exacerbating challenges in animal husbandry and contributing to pollution from the food industry, which poses certain risks to animal growth and development. However, the toxicological effects of LCCPs exposure on poultry remain inadequately understood. The liver is a critical organ in poultry, serving not only as the largest digestive gland but also as the center of metabolism. Consequently, this study employed primary chicken embryo hepatocyte as a model to investigate the toxicological effects of LCCPs exposure and its potential mechanisms of action. Our findings indicate that the proliferation capacity of primary chicken embryo hepatocytes exposed to LCCPs at concentrations of 1, 10, and 100 μg/L was significantly diminished, with an observed arrest in the G0/G1 phase and a notable reduction in the proportion of cells in the G2/M phase. Additionally, we observed that LCCPs exposure markedly decreased the autophagy levels in primary chicken embryo hepatocytes while significantly increase the levels of apoptosis. To elucidate the molecular mechanisms underlying LCCP-induced apoptosis in these cells, we assessed oxidative stress levels (ROS) and mitochondrial membrane potential, and found that the level of ROS was significantly increased, and the level of mitochondrial membrane potential was significantly decreased in primary chicken embryo hepatocytes after exposure to LCCPs. To further clarify whether LCCPs induced apoptosis in primary chicken embryo hepatocytes through oxidative stress, oxidative stress inhibitors (NAC) were used, and it was found that apoptosis caused by LCCPs exposure was significantly alleviated. These data suggest that LCCPs exposure could induce apoptosis in primary chicken embryo hepatocytes through oxidative stress. In conclusion, the current work shows that LCCPs have multiple toxic effects on primary chicken embryo hepatocytes, and lays a theoretical foundation for future research on the harmful effects of LCCPs in the poultry industry.